Mangrove Health Based on Fauna Biodiversity in Bobo Village, Jailolo District, West Halmahera Regency - Abubakar, Salim; Rina, Rina; Subur, Riyadi; Susanto, Adi Noman; Kodung, Faisal Rivai (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The health of the mangrove forest ecosystem is related to vegetation cover and faunal biodiversity is one of the indicators in the assessment of mangrove health. The research aims to determine the composition of mangrove species and mangrove forest fauna, determine the condition of mangrove forests based on the density of mangrove species, determine animal community structures which include biodiversity and dominance and determine the health level of mangroves in Bobo Village, Jailolo District. The sampling method of mangrove species was using the line transect method, while the health condition of the mangroves was a modification of FHM (Forest Health Monitoring). Fauna biodiversity data collection using the cluster method. The composition of mangrove species in Bobo Village is 6 species (Rhizophora apiculata, R. stylosa, Bruguiera gymnorrhiza, Ceriops tagal, Sonneratia alba, Xylocarpus granatum). The composition of fauna species consists of 25 species consisting of Epifauna (Gastropods = 17 species, Bivalve = 1 species, Crustaceans = 1 species) and birds (6 species). The condition of mangrove vegetation is classified as good with very dense density. The diversity of fauna in the medium category and no species is dominant. The health status of the mangrove forest in Bobo Village has 33% good, 25% moderate and 42% poor conditions.